Hubungan Faktor- Faktor Keputusan Kredit dan Potensi Gagal Bayar Pada Platform P2P Lending - Chita Oktapriana; Lucia Ari Diyani; Dade Nurdiniah (Jurnal Akuntansi dan Keuangan, 2023)
The purpose of this research is to find out whether there is a relationship between educational background, economic motivation and credit installment literacy on the interest of the younger generation to apply for credit online and to the potential for default on these online loans. The target in this study is the younger generation at school age in the city of Bekasi in the age range of 15 to 29 years. This research is a canonical correlation study using primary data. In this study, there are 3 dependent variables, namely educational background, economic drive and literacy in online credit installment calculations and 2 independent variables. Meanwhile, the 2 independent variables consist of online credit decisions and the potential for default. Based on the results of the weight test, a relationship was found between educational background and the potential for default. More specifically, in the canonical structure test, it was found that there was a relationship with a strong influence between educational background and online credit installment literacy on credit applications and the potential for default in the reverse direction.